Two New Faces of Amifostine: Protector from DNA Damage in Normal Cells and Inhibitor of DNA Repair in Cancer Cells - Hofer, Michal; Falk, Martin; Komůrková, Denisa; Falková, Iva; Bačíková, Alena; Klejdus, Bořivoj; Pagáčová, Eva; Štefančíková, Lenka; Weiterová, Lenka; Angelis, Karel J; Kozubek, Stanislav; Dušek, Ladislav; et al. (Journal of medicinal chemistry, 2016)
Amifostine protects normal cells from DNA damage induction by ionizing radiation or chemotherapeutics, whereas cancer cells typically remain uninfluenced. While confirming this phenomenon, we have revealed by comet assay and currently the most sensitive method of DNA double strand break (DSB) quantification (based on γH2AX/53BP1 high-resolution immunofluorescence microscopy) that amifostine treatment supports DSB repair in γ-irradiated normal NHDF fibroblasts but alters it in MCF7 carcinoma cells. These effects follow from the significantly lower activity of alkaline phosphatase measured in MCF7 cells and their supernatants as compared with NHDF fibroblasts. Liquid chromatography-mass spectrometry confirmed that the amifostine conversion to WR-1065 was significantly more intensive in normal NHDF cells than in tumor MCF cells. In conclusion, due to common differences between normal and cancer cells in their abilities to convert amifostine to its active metabolite WR-1065, amifostine may not only protect in multiple ways normal cells from radiation-induced DNA damage but also make cancer cells suffer from DSB repair alteration.
Keywords: Microscopy, Fluorescence; Alkaline Phosphatase; MFC-7 buňky; Humans; 53BP1; Gamma Rays; DNA Breaks, Double-Stranded; alkalická fosfatasa; histony; dvouřetězcové zlomy DNA; oprava DNA; intracelulární signální peptidy a proteiny; radioprotektivní látky; Radiation-Protective Agents; fluorescenční mikroskopie; Amifostine; záření gama; Tumor Suppressor p53-Binding Protein 1; lidé; Mercaptoethylamines; DNA Repair; merkaptoethylaminy; Comet Assay; Intracellular Signaling Peptides and Proteins; Histones; poškození DNA; DNA Damage; fibroblasty; amifostin; kometový test; Fibroblasts; MCF-7 Cells